2000
DOI: 10.1021/jp001715r
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Behavior and Formation of Surface Relief Grating on Self-Assembled Polyion/Dye Composite Film

Abstract: Holographic surface relief gratings (SRGs) were fabricated on composite films assembled by electrostatic layer-by-layer (ELBL) deposition of a polyelectrolyte, poly(dimethyl diallylammonium chloride) (PDAC), and an azo dye, Congo Red (CR). Surface modulation and first-order diffraction efficiency of the SRG were found to increase with the thickness of the PDAC/CR films. Polarized absorption spectra indicated an oriented growth of CR on the PDAC film. Analysis of the film thickness, FTIR, and FT-Raman results c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 75 publications
4
48
1
Order By: Relevance
“…The red-shift of λ max due to the CR aggregation has also been widely reported [42][43][44]. For example, Yamaki et al [45] have reported the λ max of the CR red-shift to 504 nm upon forming aggregates in a layer-by-layer nanostructured film under a given condition.…”
Section: Uv-vis Absorption Spectramentioning
confidence: 74%
“…The red-shift of λ max due to the CR aggregation has also been widely reported [42][43][44]. For example, Yamaki et al [45] have reported the λ max of the CR red-shift to 504 nm upon forming aggregates in a layer-by-layer nanostructured film under a given condition.…”
Section: Uv-vis Absorption Spectramentioning
confidence: 74%
“…The LBL technique is based on the spontaneous adsorption of charged species from solution onto a solid substrate, with the mechanism responsible for adsorption being in most cases ionic interactions. An overall understanding of the adsorption mechanisms for LBL film fabrication has become a key to the development of films with specific and optimized properties for optoelectronics and photonics [9][10][11][12] and sensing [13][14][15][16]. A detailed investigation of adsorption processes in polymeric LBL films requires the knowledge of several factors, including polymer-polymer, polymer-solvent, and polymer-substrate interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The location of these functional units (which may be small molecules, pendants on the polyelectrolyte chains, or particles) within the multilayer stack can be controlled with subnanometer precision. A wide variety of functionalities have been demonstrated, including organic molecules (He et al, 2000a), synthetic polymers , biopolymers (Burke and Barrett, 2003b), natural proteins (Caruso and Mo¨hwald, 1999), colloids (Lvov et al, 1997), inorganic nanoparticles (Kotov et al, 1995), clay platelets (Kleinfeld and Ferguson, 1994) (used as a nacre biomimic [Tang et al, 2003]), dendrimers (Watanabe and Regen, 1994), electrochemically active species (Knoll, 1996), functionalized C 60 (Mattoussi et al, 2000), and even, counterintuitively, uncharged and nonpolar polymer chains (Rouse and Ferguson, 2002). Many research groups have investigated the possibility of incorporating optically responsive azobenzene chromophores into the versatile PEM structures (examples presented in Fig.…”
Section: Polyelectrolyte Multilayersmentioning
confidence: 99%